Natural Gas in Central and Southeastern Europe: Market Unification and New Challenges - Giday, András; Fritsch, László (Public Finance Quarterly, 2022)
Gas consumption and its source are a strategic issue for all European countries. Our study examines the consumption of natural gas in Central and Southeastern Europe, the level and structure of consumption in the region, and analyses the network developments and the construction of LNG ports over the past decade and a half. The rules adopted by the EU created a unified market by providing access to the use of the network. Since the construction of natural gas pipelines in the 1970s, gas imports from Russia have played a dominant role in the supply of Central and Southeastern Europe. In the last 10–2 years, further large capacity pipelines have been built from the east to Europe, which created an opportunity for new connection points for the countries in the region. With the interconnectors built between the individual countries of the region, the market of the region can be now considered unified, where access to the network is provided at moderate costs. At the same time, the consumption and transport of natural gas in the region have been and still are highly politicised issues. On the one hand, the new climate policy concepts and agreements announced have a considerable impact and, on the other hand, geopolitical tensions also affect the transport of natural gas. In 2021, an increase in consumption was still likely. This was due to the fact that the states in the region wished to shift from coal-fired power plants to electricity generation based on a combination of renewables and natural gas, while the new southern pipelines in the Balkans would have allowed for greater imports than before. In the changed circumstances, the previously planned level of natural gas use is expected to be reduced. High prices and the fact that access to Russian gas imports may even be limited due to the atmosphere reminiscent of the Cold War are also factors that point in this direction.